Algae potential resource assessment for the energy and chemistry sectors in France by 2030 - Kerlero De Rosbo, Guillaume; Payen, Luc; Bernard, Olivier; Mairet, Francis; Grimaud, Ghjuvan ; 0000-0003-2752-4755; Delclaux, Etienne; Rey, David; Ras De Moncuit, Monique; Houdon, Aude-Claire; Gagnepain, Bruno; Gueudet, Alice; El Khamlichi, Aicha; et al. (IAEA, 2014)
To address environmental and climate issues, alternative technologies to fossil resources are sought after, both for the production of fuels and of chemicals. Algae appear as an attractive solution and have applications in the food, feed, energy or chemistry at large. A study funded by ADEME and conducted by ENEA, a consulting firm for energy and sustainable development for the industrial sector, in partnership with INRIA assessed the potential of algal French resources (micro- and macro-algae) for the production of advanced bio-fuels and molecules of interest (bio-plastic, nutrients etc.) in 2030. This assessment is based both on a model of the French national resources (physical production potential without the use of agricultural land) and what the we now know of the markets concerned and their projection 2030. The analysis shows a physical potential output of up to 9% of the French bio-diesel consumption in 2030 and enough to supply many European markets in algal bio-products. R and d efforts are however required to achieve sufficient technical and economic performance to fully exploit this potential
Report number: INIS-FR--16-0054